Implications of reactive oxygen species on cancer formation and its treatment - Shah, Manish A; Rogoff, Harry A (Seminars in oncology, 2021)
Elevated levels of reactive oxygen species (ROS) are a hallmark of cancer. Although increased ROS concentrations play important roles in cancer formation and progression, levels above a cytotoxic threshold cause cancer cell death. Cancer cells adapt to high concentrations of ROS via antioxidant production and reprogrammed cellular metabolism (eg, the Warburg effect). Because some widely used anticancer therapies such as radiation therapy and chemotherapy rely on ROS accumulation as a mechanism to induce cancer cell death, a cancer cell's ability to control ROS levels is a driver of treatment resistance and a critical consideration for successful cancer treatment. The necessity for cancer cells to adapt to elevated levels of ROS to survive may represent an Achilles heel for some malignancies, as therapies designed to interfere with this adaptation would be expected to kill cancer cells. In this review, we provide an overview of the implications of ROS on cancer formation and anticancer treatment strategies, with a focus on treatment-resistant disease.